Mengajarkan Iman Melalui Budaya: Strategi PAK Kontekstual Berbasis Tradisi Yaki-Yaki Dan Wolay - Fanrisa Sumangkut; Riane Vina Sangkoy; Kevin Seroan (Jurnal Ilmiah Wahana Pendidikan, 2026)
Contemporary Christian Religious Education (CRE) in Minahasa is confronted with cultural alienation, where faith dogmas are often taught in an isolated-ascetic manner, detached from local cultural realities. The current of globalization worsens this identity crisis among the youth. This study aims to formulate a transformative and integrative Contextual CRE strategy by exploring two Minahasa cultural traditions within the Kuncikan Festival: the Yaki-yaki tradition in Ranomea and the Wolay tradition in Poopo Village. This study employs a descriptive qualitative method utilizing a literature review and a reflective-theological-pedagogical analysis of cultural texts. The analysis demonstrates that the Yaki-yaki tradition embodies pedagogical values of simplicity, social equality, solidarity, and hospitality. Meanwhile, the Wolay tradition transmits values of historical struggle, ecological theology awareness, ethical discipline, and communal thanksgiving. Integrating both traditions through a three-dimensional time praxis model (past, present, future) deconstructs church biases against local culture while reconstructing CRE learning into an aesthetic, communal, and contextual staging of Kingdom of God values.